Factors affecting dry matter intake by lactating dairy cows - John F. Smith; Michael J. Brouk (Kansas Agricultural Experiment Station Research Reports, 2000)
Feed intake is the single most critical factor of dairy production, and performance of dairy cattle can be enhanced or hindered by environmental factors that affect it. These environmental factors can by divided into physical and climatic conditions. On modern dairies, the physical factors may be of more concern. Modern facilities provide the cow with protection from the natural elements. However, these same facilities can enhance or hinder dry matter intake. Facilities should provide adequate access to feed and water, a comfortable resting area, and adequate protection from the natural elements. Critical areas of facility design related to feed intake include access to feed and water, stall design and surface, supplemental lighting, ventilation, and cow cooling. The total system should function to enhance cow comfort and intake. It is important to remember that choices made during construction of a facility will affect the performance of animals for the life of the facility, which is generally 20 to 30 yr. Producers, bankers, and consultants too often view the additional cost of cow comfort from the standpoint of initial investment rather than long-term benefit.; Dairy Day, 2000, Kansas State University, Manhattan, KS, 2000;
Keywords: Dairy Day; 2000; Kansas Agricultural Experiment Station contribution; no. 01-166-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 861; Dairy; Facilities; Cows; Enviromental stress